A systematic review on the role of melatonin and its mechanisms on diabetes-related reproductive impairment in non-clinical studies - Armandeh, Maryam; Bameri, Behnaz; Haghi-Aminjan, Hamed; Foroumadi, Roham; Ataei, Mahshid; Hassani, Shokoufeh; Samadi, Mahedeh; Shayesteh, Mohammad Reza Hooshangi; Abdollahi, Mohammad (Frontiers in Endocrinology, 2022)
Background: Diabetes-induced reproductive complications can lead to subfertility and infertility, raising the need to protect reproductive organs. There are limited medications used to improve reproductive health in diabetic patients. Melatonin, mainly produced by the pineal gland, may improve diabetes-associated reproductive complications through various mechanisms and may be a preferred candidate to protect the reproductive system. The present review aims to elucidate the underlying mechanisms of melatonin's effect on the reproductive system adversely affected by diabetes mellitus (DM). Methods: A comprehensive systematic literature electronic search was done using the PRISMA guidelines. Web of Science, PubMed, Embase, and Scopus were searched for publications up to June 2022. Search terms were selected based on the study purpose and were explored in titles and abstracts. After screening, out of a total of 169 articles, 14 pertinent articles were included based on our inclusion and exclusion criteria. Results: The results of studies using rats and mice suggest that DM adversely affects reproductive tissues, including testes and epididymis, prostate, corpus cavernosum, and ovary leading to alterations in histological and biochemical parameters compared to the normal groups. Treatment with melatonin improves oxidative stress, blocks apoptosis induced by endoplasmic reticulum stress and caspase activation, reduces pro-inflammation cytokines, and enhances steroidogenesis. Conclusion: Melatonin exerted a protective action on the impaired reproductive system in in-vivo and in-vitro models of DM. The topic has to be followed up in human pregnancy cases that will need more time to be collected and approved.